Diversity and feeding guilds of fish populations in Pengkalan Gawi-Pulau Dula section of Tasik Kenyir Terengganu, Malaysia - Kamaruddin, Izharuddin Shah (2011)
This study was conducted to evaluate the species diversity and feeding habits of fish population in the Pengkalan Gawi – Pulau Dula section of Tasik Kenyir Terengganu. Samples were collected monthly from February 2008 to January 2009 (12 months) at three sampling stations designated as Station A (Pulau Dula), Station B (Sungai Ikan) and Station C (Pulau Pupi). Fish sample were collected using gill nets measures 100 m long, 3 m deep and having a stretch mesh size of 6.35 cm (2.5 inches). A total of 274 individuals fish comprising 13 species from 5 families were collected during the study period. The mean values for the Shannon-Weaver index, Pielou Evenness index and Margalef Richness index were 1.41±0.23, 0.81±0.13, 3.53±0.62 respectively. Six most dominant species namely Barbodes schwanenfeldii, Notopterus sp., Hampala macrolepidota, Hemibagrus nemurus, Channa micropeltes and Pristolepis faciatus were selected for the study on the stomach contents. Among the wide and variety prey consumed, Aquatic insect was the most important food item fed by the fish species in this ecosystem. The Aquatic insect food item was abundant in the stomach of H. nemurus thus it was categorized as insectivore fish species. Four other species comprising B. schwanenfeldii, Notopterus sp., H macrolepidota and P. faciatus consumed on balance dietary component mostly Aquatic insect, Fish food item, Plant materials and Phytoplankton. The stomach content of C. micropeltes was found with high percentage of Fish food item and it was classified as piscivore fish species with the highest Trophic Level value of 3.56±0.63. In terms of spatial distribution, Shannon-Weaver index value in Pulau Dula was the lowest when compared to the other stations. This station was inhabited by 9 species with 72 individuals fish, while Sungai Ikan was inhabited by 11 species with 128 individuals and Pulau Pupi was inhabited by 7 species with 74 individuals fish. All of the six most dominant species were present at each station and most of them were found in abundance specifically in one station, indicated that they were limited to one particular habitat. Temporally, the three most dominant species included B. schwanenfeldii, Notopterus sp. and H. macrolepidota were present in the monthly samples throughout the study period. The results of this study indicated that most of the species found were similarly reported in other studies in Tasik Kenyir. It is hoped that the results will be useful in contributing towards management of the lake in a sustainable manner for future generations.